Selection of Best Consultant by using Analytical Hierarchy Process (AHP) - Putri Zulaiha, Razi; Noram Irwan, Ramli; Mohamad Idris, Ali; Putra Jaya, Ramadhansyah (IOP Publishing, 2020)
Consultant selection is a complex problem involving qualitative and quantitative multi criteria decision. In this study, an AHP-based consultant selection model is applied to develop and assist in decision making process to resolve the consultant selection problem in choosing the most favourable consultant's criteria combination. The Analytic Hierarchy Process (AHP) is an established decision method used to synthesize judgements and select the best alternative. When the objectives and scopes of study are set, then the data collection are made through two methods which are through literature review and pair-wise questionnaire survey. Information obtained from the questionnaire is interpreted into a simpler form and analysed by using the Expert Choice software. Results shows that financial capability of the consultant prioritize the decision of the selection while dominating the sub-criteria for selection is the profit made by the consultant within the last 3 years.